MRI of prostate stem cell antigen expression in prostate tumors. (May 2012) - Ren, Jing; Zhang, Zhuoli; Wang, Fang; Yang, Yong; Liu, Ying; Wei, Guangquan; Yang, Angang; Zhang, Rui; Huan, Yi; Cui, Yali; Larson, Andrew C
Background: The prostate stem cell antigen (PSCA) is broadly overexpressed on the surface of prostate cancer cells.Materials & methods: Anti-human PSCA monoclonal antibody (mAb 7F5) was bound to Fe3 O4 /Au (GoldMag) nanoparticles to serve as a PSCA-specific molecular MRI probe (mAb 7F5@GoldMag) for in vivo detection of prostate cancer cells. First, the efficacy of the antibody immobilization for the binding was assessed. Next, PC-3 (human prostate cancer cell line with PSCA overexpression) tumor-bearing mice were injected with mAb 7F5@GoldMag for MRI measurements while using mouse anti-human IgG bound to the particles (IgG@GoldMag) to serve as a nonspecific control. MRI examinations were conducted before and after injection of these probes at 6, 12 and 24 h; T2-weighted signal intensity within the tumors was measured.Results: Targeted binding of the mAb 7F5@GoldMag probe to PC-3 tumors was verified with optical images and MRI; selective binding was not observed for the nonspecific IgG@GoldMag probe.Conclusion: MRI measurements suggest the promising efficacy of this new approach for targeted molecular imaging of prostate tumors. Original submitted 5 March 2011; Revised submitted 4 July 2011